American Arabesque : Arabs and Islam in the Nineteenth Century Imaginary. - Berman, Jacob Rama (America and the long 19th century., 2012)
American Arabesque examines representations of Arabs, Islam and the Near East in nineteenth-century American culture, arguing that these representations play a significant role in the development of American national identity over the century, revealing largely unexplored exchanges between these two cultural traditions that will alter how we understand them today. Moving from the period of America's engagement in the Barbary Wars through the Holy Land travel mania in the years of Jacksonian expansion and into the writings of romantics such as Edgar Allen Poe, the book argues that not only were.